BIMBINGAN TEKNIS PEMBUATAN KOMPOS DI DESA BINAAN POLINEMA, WRINGIN SONGO, TUMPANG - Windi Zamrudy; Rosita Dwi Chrisnandari; Eko Naryono (P3M Politeknik Negeri Malang, 2022)
Wringinsongo is one of the rural areas in Tumpang District, Malang Regency, East Java Province that offers numerous advantages, particularly in the agricultural and tourism sectors. Wringinsongo's growing population, increasingly diverse consumption patterns, the establishment of modern markets, and community economic activities all contribute to increased waste generation. The volume of waste at the Wringinsongo Temporary Disposal Site (TPS) has reached 15 m3, causing environmental and social issues. The majority of the waste in TPS and TPA is organic waste generated by households. The accumulation of organic waste in TPS and TPA will produce anaerobic decomposition compounds, namely methane gas, which is the primary cause of the greenhouse effect, which has a negative impact on the environment. Composting is one method of waste processing that can be used to reduce waste in TPA and TPS. Basic composting knowledge and skills are acquired during the composting process in order to achieve the desired results. Thus, community service is provided with the intention of offering technical composting guidance. Counseling and direct practice in composting are the methods used. Counseling is used to provide insight into waste processing via composting, while practice is employed to provide skills and direction in the composting process. This activity generates initial compost, which can be added to with new organic waste every day, enables household organic waste to be managed independently.